Cattle grazing effect on Mimosa pudica L. in tropical pasture system - Ajorlo, Majid; Abdullah, Ramdzani; Abdul Halim, Ridzwan; Ebrahimian, Mahboubeh (Universiti Putra Malaysia Press, 2014)
Mimosa pudica is the most abundant and problematic invasive species in tropical pastures. This study investigates the effects of two cattle grazing systems, long-term moderate grazing (LTG, 2.7 animal unit/ha/yr for 33 years) and short-term heavy grazing (STG, 5 animal unit/ha/yr for 2 years) compared with ungrazed exclosure pasture on the invasion of M. pudica and its relationship with herbage production in tropical pasture. M. pudica and pasture production were concurrently sampled four times at the end of grass growing period at both grazed and ungrazed pastures. Mean density of M. pudica was 56% greater (P<0.05) in the LTG pasture than that in the ungrazed exclosure although it did not vary (P>0.05) between the STG pasture and ungrazed exclosure. Mean importance value (IV) of M. pudica in the LTG pasture was 46% lower (P<0.05) than that in the ungrazed exclosure, and this was 220% greater (P<0.05) in the STG pasture than that in the ungrazed exclosure. Pasture herbage production was unrelated (P>0.05) to the density, IV and dry matter (DM) of M. pudica in either pasture system. An insignificant negative relationship was found between the density and DM of M. pudica with pasture production. In contrast, a positive but insignificant relationship was observed between %IV of M. pudica and pasture production in both pasture sites. The LTG system had adverse effect on M. pudica population, whereas STG system supplied relatively desirable conditions for M. pudica establishment and infestation.